Brief Report: Sexual Violence Against HIV-Positive Women in the Nyanza Region of Kenya: Is Condom Negotiation an Instigator?. (1st January 2017) - Onu, Chinwe C.; Dworkin, Shari L.; Ongeri, Linnet G.; Oyaro, Patrick; Neylan, Thomas C.; Cohen, Craig R.; Bukusi, Elizabeth A.; Rota, Grace; Meffert, Susan M.
Abstract: For people living with HIV, exposure to sexual violence (SV) is associated with decreased adherence to antiretroviral medication, a primary predictor of their survival. Identification of risk factors for SV is a pressing issue in sub-Saharan Africa, where the global majority of HIV-positive women live and the prevalence of SV against women is high. We used qualitative data to examine SV against HIV-positive women enrolled in HIV care in Kenya. Respondents identified husbands as perpetrators of SV in the context of women's efforts to use condoms as directed by HIV care providers.